Comparing Peribulbar and Topical Anesthesia in Cataract Surgery among Patients with Cardiovascular Disease - Behera, Geeta; Kothari, Akhilesh; Subramanian, Anandaraja; Jayaraman, Ramesh; Rene, Senthamizhan (Korean journal of ophthalmology, 2024)
Purpose: To compare topical and peribulbar anesthesia in cataract surgery for hemodynamic changes, rate of complications and pain score in patients with cardiovascular disease.Methods: A prospective comparative study at a tertiary care center in India. Patients >40 years old with treated/controlled hypertension and cardiovascular disease scheduled for cataract surgery under topical or peribulbar anesthesia were recruited. Heart rate, blood pressure, and ophthalmic and systemic complications were noted: preoperatively, immediately after block, intraoperatively, immediately postoperatively and 1 hour postoperatively. A visual analog scale was used to assess the pain score.Results: A total of 150 patients (75 in each group) underwent cataract surgery. There was a significant rise in pulse rate and blood pressure after peribulbar injection and intraoperatively, which gradually reduced to baseline 1 hour after surgery in both groups (p < 0.001), with systolic blood pressure intraoperatively being significantly greater in the peribulbar group (155.49 ±18.14 mmHg vs. 147.95 ±17.71 mmHg, p = 0.01). The topical group had slightly lower visual analog scale scores (1.12 ± 0.99) than the peribulbar group (1.44 ± 0.90, p = 0.04).Conclusions: Cataract surgery appears safe in patients with adequately controlled cardiovascular disease, and topical anesthesia may be preferable due to noninvasiveness, adequate analgesia, and minimal effect on hemodynamic parameters. Therefore, hemodynamically stable patients of cardiovascular disease undergoing uncomplicated cataract surgery may be counselled for topical anesthesia.